ABOUT THE NEWSPAPER "SADOI TURKISTON" AND THE ARTICLE IN IT (Scientific journal of the Fergana State University, 2023)
This article discusses the newspaper "Sadoi Turkestan", one of the first newspapers of Uzbek journalism. The features of the newspaper, history, issues of publishing, specific aspects of the newspaper business of that time are taken into account. The article also contains the original article by Ashurali Zahiri entitled "Ona tili" and its transliteration, which serves as a valuable resource for philologists, historians, publicists and source scholars.By studying the transliterated text, you can gain new knowledge related to the peculiarities of the Uzbek language of that time, the construction of the text, and the history of publishing.